Leukoreduction in a dog with acute leukemia - Brenna Hanratty; Anna Hauck; Amanda Foskett; J. D. Foster (Journal of Veterinary Internal Medicine)
Abstract A 9‐year‐old male castrated golden retriever cross was evaluated for an acute onset of ataxia. A complete blood count revealed marked leukocytosis, anemia, and thrombocytopenia. Leukocytosis was characterized by marked lymphocytosis, monocytosis, neutropenia, and eosinopenia. Flow cytometry identified CD34+ leukocytosis with cells that did not express lineage antigens, suggesting the most likely diagnosis of either acute lymphoid or myeloid leukemia. Leukoreduction via leukapheresis was elected to reduce the disease burden before initiating chemotherapy. Postleukoreduction, the dog had a 54% decrease in their white blood cell count. The dog completed multiple weeks of traditional cyclophosphamide, doxorubicin, vincristine, prednisone (CHOP)‐based treatment and had a survival time of 43 days before the owner elected humane euthanasia. To our knowledge, this report represents a case of acute leukemia in a dog treated with leukoreduction before starting chemotherapy.